Functions and Duties of the KPU in Increasing Community Political Participation - Kamariani, Baiq Dewi; Hartiani, Hartiani; Hartati, Widya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The general election commission (KPU) has an important role in facilitating a democratic and inclusive general election process. The main functions of the KPU, such as preparing general election lists, disseminating general election information, monitoring campaign implementation, and transparent vote counting are key factors in increasing public political participation. The research method used is a qualitative research method. The research location is the general election commission in East Lombok district. The research data sources are primary data and secondary data using observation, interview and documentation data collection techniques. The research results show that the implementation of the functions and duties of the general election commission in increasing community political participation in East Lombok district is good. Based on data from the 2024 DPT final election list, there is more political participation from the public compared to the previous year.